2012
DOI: 10.5817/bse2012-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Causal and Contrastive Discourse Markers in Novice Academic Writing

Abstract: Causal and contrastive relations between adjacent or more distant segments of discourse play an important role in expressing coherence relations (Taboada 2006) in academic discourse including discourse written by university students of English. By overtly signalling how the writer intends the discourse segment that follows to relate to the previous segment(s), discourse markers (DMs), in particular those expressing causal and contrastive relations, contribute to cohesion and enhance the establishment and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
2
27
0
3
Order By: Relevance
“…This finding is in line with Sitthirak (2013, p. 875), who asserted that "Thai learners found a variety of DMs difficult to distinguish and the apparent interchangeability of the CDMs can also be the cause of confusion". Additionally, the finding that 'but' was the most frequent CDMs used in this study also resonated and supported other studies, which revealed the extreme reliance on the use of 'but' among EFL learners, such as the studies of Povolná (2012) and Dumlao and Wilang (2019).…”
Section: Contrastive Discourse Markers (Cdms)supporting
confidence: 88%
See 1 more Smart Citation
“…This finding is in line with Sitthirak (2013, p. 875), who asserted that "Thai learners found a variety of DMs difficult to distinguish and the apparent interchangeability of the CDMs can also be the cause of confusion". Additionally, the finding that 'but' was the most frequent CDMs used in this study also resonated and supported other studies, which revealed the extreme reliance on the use of 'but' among EFL learners, such as the studies of Povolná (2012) and Dumlao and Wilang (2019).…”
Section: Contrastive Discourse Markers (Cdms)supporting
confidence: 88%
“…Therefore, it is worth noting that the proper understanding of DMs is considered necessary for good writing production. In other words, an awareness of discourse markers will assist EFL learners in producing an effective and coherent piece of writing (Povolná, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tačiau, kaip pastebi Traugott ir Dasheris (2002: 154), daugelis diskurso žymiklių nėra apriboti tam tikro diskurso tipo, jie randami įvairiuose tekstuose, įskaitant ir formalųjį rašytinį diskursą. Diskurso žymikliai tyrinėti įvairiose rašytinės akademinės kalbos atmainose (Bondi 2004;Povolná 2012;Rezanova, Kogut 2015), dalis Furkó (2020) diskurso žymiklių tyrimo skirta jų vartosenai verslo anglų kalbos vadovėliuose, Lansari (2020) pasitelkia internete esančių tekstų (forumų, blogų, laikraščių straipsnių) tekstyną sakymo diskurso žymiklių (angl. discourse markers of saying) anglų ir prancūzų kalbose analizei.…”
Section: į Va D a Sunclassified
“…BLP 1 uses 6 contrastive DMs over the total observation period, whereas 14 contrastive DMs are found on BLP2's status updates and 7 contrastive DMs are employed by BLP 3. Whereas the contrastive DMs are used by the participants within the discursive space of mini-narratives that reflect their everyday routines, these DMs seem to signal that "there is a sense of dissonance" (Fraser 1988: 30;Povolná 2012). For instance, when the participant BLP 3 writes about going out to see a film with the actor Russell Crowe, she indicates that "I'm not a fan.…”
Section: The Use Of the English Dms By The Participantsmentioning
confidence: 99%